Novel 5-oxo-hexahydroquinoline derivatives: design, synthesis, in vitro P-glycoprotein-mediated multidrug resistance reversal profile and molecular dynamics simulation study - Shahraki O; Edraki N; Khoshneviszadeh M; Zargari F; Ranjbar S; Saso L; Firuzi O; Miri R (Dove Medical Press, 2017)
Omolbanin Shahraki,1,2 Najmeh Edraki,1 Mehdi Khoshneviszadeh,1,2 Farshid Zargari,1 Sara Ranjbar,1,2 Luciano Saso,3 Omidreza Firuzi,1 Ramin Miri1 1Medicinal and Natural Products Chemistry Research Center, 2Department of Medicinal Chemistry, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 3Department of Physiology and Pharmacology “Vittorio Ersparmer”, Sapienza University of Rome, Rome, Italy Abstract: Overexpression of the efflux pump P-glycoprotein (P-gp) is one of the important mechanisms of multidrug resistance (MDR) in many tumor cells. In this study, 26 novel 5-oxo-hexahydroquinoline derivatives containing different nitrophenyl moieties at C4 and various carboxamide substituents at C3 were designed, synthesized and evaluated for their ability to inhibit P-gp by measuring the amount of rhodamine 123 (Rh123) accumulation in uterine sarcoma cells that overexpress P-gp (MES-SA/Dx5) using flow cytometry. The effect of compounds with highest MDR reversal activities was further evaluated by measuring the alterations of MES-SA/Dx5 cells’ sensitivity to doxorubicin (DXR) using MTT assay. The results of both biological assays indicated that compounds bearing 2-nitrophenyl at C4 position and compounds with 4-chlorophenyl carboxamide at C3 demonstrated the highest activities in resistant cells, while they were devoid of any effect in parental nonresistant MES-SA cells. One of the active derivatives, 5c, significantly increased intracellular Rh123 at 100 µM, and it also significantly reduced the IC50 of DXR by 70.1% and 88.7% at 10 and 25 µM, respectively, in MES-SA/Dx5 cells. The toxicity of synthesized compounds against HEK293 as a noncancer cell line was also investigated. All tested derivatives except for 2c compound showed no cytotoxicity. A molecular dynamics simulation study was also performed to investigate the possible binding site of 5c in complex with human P-gp, which showed that this compound formed 11 average H-bonds with Ser909, Thr911, Arg547, Arg543 and Ser474 residues of P-gp. A good agreement was found between the results of the computational and experimental studies. The findings of this study show that some 5-oxo-hexahydroquinoline derivatives could serve as promising candidates for the discovery of new agents for P-gp-mediated MDR reversal. Keywords: cancer, P-glycoprotein, multidrug resistance, 1,4-dihydropyridine, molecular dynamics simulation